Violation of consolidation of the femur after untimely dynamization of the intramedullary blocking rod - Chabanenko, Diomyd; Polіvoda Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2021)
Violation of femoral fracture consolidation after blocking intramedullary osteosynthesis is a fairly common pathology, and requires the attention of physicians due to its prevalence. There are several reasons for this complication: it is the instability in the system «bone-implant», and the untimely dynamization of the locking nail. Methods. This article presents a case of fracture violated consolidation after blocking intramedullary osteosynthesis caused a nonunion due to nail failure. Results. Patient was injured on 29.12.2018, as a result of a traffic accident. 01.15.2019, the surgery was performed: closed reduction, blocking intramedullary osteosynthesis of the fracture of the middle shaft of the right thigh, static fixation of the nail. Next visit to the clinic was on 02.01.2020, because of pain in the middle third of the thigh, problems with axial weight-bearing on the right leg, limitation of the flexion in the right knee joint. Control radiographs demonstrated no signs of consolidation of the femoral shaft fracture, and migration of the distal locking screw. 08.01.2020 revision surgical treatment was performed. Given the presence of 5 mutually perpendicular holes in the distal part of the nail, two of them were locked in the anterio-posterior view by the free hand method, the migrated screw in the distal part of the nail was replaced, and the nail was dynamized in the proximal part taking into account its design features. Conclusions. To normalize the consolidation processes in patients with nonunion femoral fractures, bone physiology and the positive effect of autocompression should be considered. The described case demonstrates the necessity for timely dynamization of the blocking nail, which confirms our own observations and literature data. Despite the fact that the dynamization of the nail was performed 1 year after blocking intramedullary osteosynthesis, fracture consolidation occurred 5 months after its implementation. Key words. Femoral fracture, blocked intramedullary osteosynthesis, disorders consolidation, dynamization of the construction.